2020
DOI: 10.1007/s10096-020-03870-3
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study

Abstract: An accurate knowledge of the epidemiology of community-acquired pneumonia (CAP) is key for selecting appropriate antimicrobial treatments. Very few etiological studies assessed the appropriateness of empiric guideline recommendations at a multinational level. This study aims at the following: (i) describing the bacterial etiologic distribution of CAP and (ii) assessing the appropriateness of the empirical treatment recommendations by clinical practice guidelines (CPGs) for CAP in light of the bacterial pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…A subsequent study using a novel serotype-specific urinary antigen detection assay in 1736 samples coming from the EPIC trial identified additional 76 (4.4%) cases of pneumococcal CAP [ 11 ]. Similar results were provided by the Global Initiative for Methicillin-resistant S. aureus Pneumonia (GLIMP) point-prevalence international study among 2564 patients hospitalized with CAP in 2015; S. pneumoniae was detected in 8.2% followed by P. aeruginosa (4.1%) and K. pneumoniae (3.45), whereas in 35.3% no pathogen was detected [ 12 ]. Many patients of the PROGRESS trial were found with bacterial and viral co-infection.…”
Section: Discussionsupporting
confidence: 76%
“…A subsequent study using a novel serotype-specific urinary antigen detection assay in 1736 samples coming from the EPIC trial identified additional 76 (4.4%) cases of pneumococcal CAP [ 11 ]. Similar results were provided by the Global Initiative for Methicillin-resistant S. aureus Pneumonia (GLIMP) point-prevalence international study among 2564 patients hospitalized with CAP in 2015; S. pneumoniae was detected in 8.2% followed by P. aeruginosa (4.1%) and K. pneumoniae (3.45), whereas in 35.3% no pathogen was detected [ 12 ]. Many patients of the PROGRESS trial were found with bacterial and viral co-infection.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings show that the expected effects are congruent with this intention.. Presumably more frequently culturing the "right" patients would increase the overall diagnostic yield [24][25][26]. However, we estimated that 370 (26%) of MRSA and 479 (36%) of P. aeruginosa cases would be "missed" by guideline recommended culturing on hospital wards, including 45 (11%) of cases of MRSA bacteremia.…”
Section: Discussionsupporting
confidence: 64%
“…Studies from our center have shown atypical pathogens are more common in the etiology of pneumonia [ 18 ], however, recently, amongst cultivable organisms, Staphylococcus aureus was the most common pathogen causing pneumonia, with S. pneumoniae and P. aeruginosa being close seconds [ 19 ]. Another study looking at bacterial etiology of pneumonia in immunocompetent hospitalized patients showed Pseudomonas aeruginosa to be the most common causative agent in Pakistan [ 20 ]. Only 2 samples were positive for Streptococcus pneumoniae, historically considered the most common etiologic agent of CAP worldwide.…”
Section: Discussionmentioning
confidence: 99%